IMPLEMENTATION OF THE MERDEKA CURRICULUM FOR ISLAMIC RELIGIOUS EDUCATION SUBJECT - Batubara, Rubiyah; Ananda, Rusydi; Salim, Salim (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Purpose: The aim of this study is to analyze the planning, implementation, and evaluation of Islamic Religious Education (PAI) as part of the Merdeka Curriculum. Method: This research employed a qualitative method with a multisite approach at SMA Negeri 1 and SMA Negeri 4 Padangsidimpuan. The analysis technique followed Miles, Huberman, and Saldana (2014), consisting of data condensation, data presentation, and conclusion drawing. Result: The findings reveal that: (1) lesson planning in both schools adheres to the national Merdeka Curriculum guidelines, yet differs in practice—SMA Negeri 1 combines conventional planning with selective innovations, while SMA Negeri 4 emphasizes project-based and contextual approaches tailored to student needs; (2) the implementation stage shows strong institutional commitment, use of the Merdeka Teaching Platform, and student-centered learning, although challenges persist in aligning Islamic values with new pedagogical models; and (3) evaluation incorporates cognitive, affective, and psychomotor assessments, but teachers face difficulties in ensuring fairness and meaningfulness, particularly in online and hybrid settings. Conclusion: These results indicate that successful implementation of the Merdeka Curriculum depends on adaptability to local school contexts, availability of resources, and continuous teacher training. The study recommends enhancing professional development, strengthening school-community collaboration, and developing more holistic assessment strategies to ensure that Islamic Religious Education under the Merdeka Curriculum achieves its transformative goals.